2013
DOI: 10.1016/j.ccr.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Location, Location, Location: Macrophage Positioning within Tumors Determines Pro- or Antitumor Activity

Abstract: Macrophages infiltrate hypoxic tumor regions where they promote angiogenesis and immunosuppression. In this issue of Cancer Cell, Mazzone and colleagues report that tumor–associated macrophage (TAM)entry into avascular tumor areas is regulated by Semaphorin 3A/Neuropilin-1 signaling;interference with this pathway entraps TAMs in oxygenated areas preventing their tumorigenic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 10 publications
2
33
0
Order By: Relevance
“…8 Moreover, our data clearly demonstrate that macrophages can exert tumor-promoting activities, such as inducing EMT in the pancreatic ductal epithelium, by exerting pro-inflammatory properties of similar magnitude, or even stronger than, their pronounced antiinflammatory phenotype, substantiating the view that distinct modes of inflammation contribute to tumor initiation and progression (Fig. 1).…”
supporting
confidence: 57%
“…8 Moreover, our data clearly demonstrate that macrophages can exert tumor-promoting activities, such as inducing EMT in the pancreatic ductal epithelium, by exerting pro-inflammatory properties of similar magnitude, or even stronger than, their pronounced antiinflammatory phenotype, substantiating the view that distinct modes of inflammation contribute to tumor initiation and progression (Fig. 1).…”
supporting
confidence: 57%
“…This study also demonstrated that Sema3A and its receptors mediate the migration through activation of vascular endothelial growth factor receptor (VEGFR). Similar results even suggested that Sema3A/NRP-1 signaling was involved in the macrophage reprogramming [64]. Expression of Sema3A and its receptors have been identified on monocyte-derived macrophages [65].…”
Section: Macrophage and Nerve Interaction In Endometriosismentioning
confidence: 67%
“…Localization of macrophages within tumors appears to be critically important for their function and activation state (39)(40)(41). In the MIP-2 overexpression model, reduced macrophage activation in Hpa-KO tumors (Fig.…”
Section: Discussionmentioning
confidence: 94%